Electroanalytical Methodology for the Direct Determination of 2,4-Dichlorophenoxyacetic Acid in Soil Samples Using a Graphite-Polyurethane Electrode - Fernanda Ramos de Andrade; Renata Alves de Toledo; Carlos Manoel Pedro Vaz (International Journal of Electrochemistry)
An electroanalytical methodology was developed for the direct determination of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) using a graphite-polyurethane composite electrode and square wave voltammetry (SWV). 2,4-D exhibited one reduction peak with characteristics of an irreversible process at −0.54 V (versus Ag/AgCl), which is controlled by the diffusion of the reagent on the electrode surface. After the experimental parameters optimization (pH 2.0, f=50 s−1, a=0.50 V, and ΔEi=0.03 V), analytical curves were constructed in the range of 0.66 mg L−1 to 2.62  mg L−1. Detection (LD) and quantification (LQ) limits were 17.6 μg L−1 and 58.6 μg L−1, respectively. The methodology was successfully applied to measure the percolation of the herbicide 2,4-D in undisturbed soil columns of different granulometric compositions.